Mercado Imobiliário informal e seus mecanismos de operação: Vila Acaba Mundo, Belo Horizonte - Gustavo Barreto Cyrillo (2011)
Despite of the informal real state market that exists in most part of Brazilian cities and the fact that this market is the way of access to an habitation for a considerable portion of the population, there aren`t many studies made about this subject. Most of the academic investigations about this market let us with a lacuna that needs to be answered: it deals with the comprehension of how the informal real state market acts to the provision for habitations inside the slums. It`s understood as informal real state market the somatory of two dimensions of informality: the urban and the economic, as this market is not ruled by the urbanistic, of juridical properties , tributary, commercial or economic laws. The hypothesis raised to research is that in which the social habitation programs, beyond not contributing to the decrease of irregularity in the real state market,indeed increase and consolidate this irregularity. In this essay, we intend to discuss and deepen the questions related to this market operation mechanisms , beginning with the knowledge of its origins , based on the concepts already investigated by the authors Pedro Abramo and Nelson Baltrusis.The theoretic fundaments about the issue will be completed by a case study in the Acaba Mundo slum located in Belo Horizonte city. We also aim to contribute to the related nowadays urban planning discussions , in the scope of the adopted policies to the slum areas of Brazilian cities, more specifically in the cityof Belo Horizonte.